The effect of Tai chi on positive-activated affect in adults: a systematic review and multilevel meta-analysis of randomised controlled trials. - Yin, Jianchun; Yue, Caichao; Chen, Xiang; Tang, Lijun (International Journal of Sport & Exercise Psychology, 2023)
We extend findings from previous quantitative reviews of the effects of aerobic exercises on positive-activated affect (PAA) to evaluate the effect of Tai chi training on PAA in randomised controlled trials and to test whether effect varied according to participant features, Tai chi exposure, or characteristics of research design. English articles published before 31 December 2020 were searched according to PRISMA guidelines. Study quality was judged by using a revised Cochrane risk of bias (RoB 2) tool for RCTs. Hedges' d effect sizes were calculated, and random effect model with multilevel meta-analysis were used to estimate the pooled effect. I tests were applied to assess the heterogeneity. Moderating effects were tested by multilevel meta-regression analysis according to moderators derived from participant characteristics, Tai chi exposure, and features of research design. Publication bias was assessed by examining the funnel plot according to Egger's method. From 577 articles, 32 RCTs articles were selected involving 2950 adults (18 years old and above), from which 61 effects were yielded. Tai chi training significantly increased PAA in adults by a heterogeneous standardised mean effect size of 0.41 (95% CI, 0.14 to 0.69, p < 0.01). Larger effects were found when (1) higher frequency (sessions/week) of Tai chi practice was implemented, and (2) when Tai chi versus no treatment, usual care or wait-list condition was compared. Tai chi has small-to-medium efficacy for nurturing PAA. Tai chi with higher frequency and against no treatment, usual care or wait-list condition, achieve the larger PAA-generating effects.